2006
DOI: 10.1111/j.1464-410x.2006.06497.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased preoperative serum C‐reactive protein level predicts a poor prognosis in patients with localized renal cell carcinoma

Abstract: analyses the difference was considered significant when P < 0.05. RESULTSThe median (range) follow-up was 55 (2-187) months; 26 patients (26%) had high CRP levels, and 12 (46%) of these and three (4.0%) of the remaining 75 died from disease. The 5-and 10-year disease-specific survival rates (75% and 30%, respectively) in patients with high CRP levels were significantly worse than those in patients with normal CRP levels (both 93%, P < 0.001). In other variants, preoperative haemoglobin concentration, pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 20 publications
4
66
1
Order By: Relevance
“…Moreover, the extent of elevation of CRP levels in these diseases was also greater than that in other diseases. It has been reported that elevated CRP concentrations are also commonly observed in patients with neoplastic [10] and immune-mediated diseases in human medicine [7,9]. However, we have to consider that the frequency of the diseases studied was biased since this study was conducted at a teaching hospital in a university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the extent of elevation of CRP levels in these diseases was also greater than that in other diseases. It has been reported that elevated CRP concentrations are also commonly observed in patients with neoplastic [10] and immune-mediated diseases in human medicine [7,9]. However, we have to consider that the frequency of the diseases studied was biased since this study was conducted at a teaching hospital in a university.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the CRP concentration along with WBC counts is clinically valuable as a screening test for new patients to detect inflammation. In human medicine, CRP has been reported to indicate the severity and prognosis of various diseases [9,10,16,17]. In veterinary medicine, it has been reported to indicate the response to treatment and prognosis in idiopathic polyarthritis [14].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year RFS and CSS rates in patients with elevated CRP levels were 55.8 and 75.4%, respectively, compared with 93.1 and 94.8%, respectively, in patients without CRP elevation (P < 0.0001). 42 Lambs et al observed that elevation of CRP levels (>10 mg/L) was linked to poorer CSS in 100 RCC patients without metastasis. 41 Thereafter, they showed the significance of CRP elevation (>10 mg/L) to predict poorer RFS and CSS in a prospective study with 83 RCC patients undergoing curative nephrectomy.…”
Section: Prognostic Value Of Crp In Renal Cell Carcinomamentioning
confidence: 99%
“…Smaller studies published in recent years which included from 40 up to 313 patients indicated that the preoperative CRP level could also be associated with RCC-specific mortality [19][20][21][22][23][24][25][26]. These smaller trials have shown a potential relationship between circulating CRP levels and tumour stage as well as a significant impact on the prognosis of patients with RCC.…”
Section: Introductionmentioning
confidence: 99%